2019
DOI: 10.1177/1120672119870740
|View full text |Cite
|
Sign up to set email alerts
|

Central retinal artery occlusion after Descemet membrane reposition by intracameral air: A case report

Abstract: Purpose: To report a case of central retinal artery occlusion after Descemet membrane reposition by intracameral air. Methods: An otherwise healthy 60-year-old woman presented with white mature cataract in her left eye. Ocular exam of both eyes was within normal limits. After an uneventful topical phacoemulsification, a moderate-grade striate keratopathy and non-planar Descemet membrane detachment was noted on first postoperative day, which was confirmed on anterior segment optical coherence tomography. The De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…It was performed using a 30-gauge syringe at the slit lamp without a side port blade [ 9 ], allowing a minimally invasive incision with probably faster recovery time. Furthermore, no partial air release was needed in our patients to avoid severe complications such as central retinal artery occlusion compared with previous studies [ 4 ]. Additionally, drainage of predescemetic fluid by stab incision on the cornea was not necessary to achieve DM attachment as previously performed in other studies [ 10 ], making this procedure quicker and easier.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…It was performed using a 30-gauge syringe at the slit lamp without a side port blade [ 9 ], allowing a minimally invasive incision with probably faster recovery time. Furthermore, no partial air release was needed in our patients to avoid severe complications such as central retinal artery occlusion compared with previous studies [ 4 ]. Additionally, drainage of predescemetic fluid by stab incision on the cornea was not necessary to achieve DM attachment as previously performed in other studies [ 10 ], making this procedure quicker and easier.…”
Section: Discussionmentioning
confidence: 91%
“…Researchers have demonstrated that 100% air descemetopexy is more effective than iso-expansile gases, with 95% success in the reattachment of DM and statistical improvement in visual acuity [ 3 ]. Nonetheless, rarely, central retinal artery occlusion occurs after full-chamber air bubble injection [ 4 ]. To reduce the adverse effects following air descemetopexy, partial air release was applied after complete air filling for a certain period [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…There was one case of CRAO reported on a healthy 60-year-old patient following pneumatic Descemetopexy (Descemet membrane reposition by intracameral air) after cataract surgery one day earlier. 50 The intracameral air bubble was partially released after 2 h. There were no reported signs of raised IOP (e.g. headache, eye pain, nausea or vomiting) during the immediate postoperative period.…”
Section: Mechanismsmentioning
confidence: 83%
“…RAO appeared to be unrelated to the type of regional block: the reported cases occurred in relation to retrobulbar blocks (40/97, 41%) 5,7,13,14,18 33 (Supplementary Table 1), peribulbar blocks (36/97, 37%) 27,32,34 –42 (Supplementary Table 2), sub-Tenon’s blocks (19/97, 20%) 16,32,39,43 49 (Supplementary Table 3), one topical local anaesthetic (1/97, 1%) 50 and one unknown local anaesthetic technique (1/97, 1%), 51 which contained no anaesthetic details.…”
Section: Retinal Artery Occlusion After Ophthalmic Surgery Under Regi...mentioning
confidence: 99%
“…Compared with 100% sterile air, longer acting gas mixtures have better stability and retention times [15,16], which may lead to better outcomes. However, longer acting gas mixtures had a higher risk for endothelial toxicity and a pupillary block even central retinal artery occlusion (CRAO) or branch retinal arterial occlusion (BRAO) [29]. To date, the success rates of descemetopexy with longer acting gas mixtures have been reported to range from 71.64-95% [16,30].…”
Section: The Modi Ed Descemetopexymentioning
confidence: 99%